Clean Water and Sanitation Policy Optimization Strategy: Study in Pangurangan Wetan Village, Cirebon Regency - Idruz Darraz Alipasya; Leni Rohida (ann4publisher@gmail.com, 2026)
Background: The problem of access to clean water and proper sanitation remains a major challenge in Panguragan Wetan Village, Cirebon Regency, characterized by inadequate water quality, environmental pollution, and low public awareness of clean and healthy living behaviors. This condition shows that the implementation of clean water and sanitation policies at the village level has not been optimal. Aim: This research aims to analyze the implementation of clean water and sanitation policies, identify factors that support and hinder their implementation, and formulate strategies to improve policies in Panguragan Wetan Village. The research method used is a qualitative approach, with data gathered through interviews, observations, and document studies. Results: Data analysis was carried out using policy implementation theory by George C. Edwards III (1980), which includes the dimensions of communication, resources, disposition, and bureaucratic structure. The results of the study show that policy implementation has not been running optimally due to weak policy communication, limited resources, low community participation, and bureaucratic structures that have not supported cross-sector coordination. Overall, the optimization of clean water and sanitation policies requires an increase in the implementation of four dimensions in an integrated manner so that the goal of improving environmental quality and community welfare can be achieved in a sustainable manner Conclusions: The implementation of clean water and sanitation policies in Panguragan Wetan Village has not run optimally due to weak communication, limited resources, low community participation, and ineffective bureaucratic coordination. Implication: The results of this study imply the need to strengthen village policies in an integrated manner through increased socialization, resource allocation, community participation, and cross-sector coordination to support sustainable sanitation.